Qualitative and quantitative analysis of the crust base structure using Kuwait gravity anomaly maps in the determination of new oil fields: DOI: 10.48129/kjs.11415 - Aladwani, Najeeb (Kuwait Journal of Science, 2022)
Kuwait state lies at the upper northeastern corner of the Arabian Plate, on the Arabian Gulf, and surrounded by Iraq from the north, the Arabian Gulf from the east, and Saudi Arabia from other sides. Kuwait settled on thick sedimentary column built from Permian age to Recent, its thickness ranges between 7 and 8 km, take the form of the underneath basement structures. Detailed information has been got about the crustal basement structure under Kuwait state from the analysis of gravity anomaly maps and its consequential depth maps. The Oasis Montaj® (Geosoft) software has been used for preparing the geologic cross-sections from the gravity profiles. The modelled cross-section provided us with the depth and structures of crustal basement rocks within 6 to 7 km under Kuwait and its associated sedimentary basins with a detailed geometry. The results can give us information about the sedimentary basins for further exploration of oil in the future. This information will be useful, in finding, extension, depth and the geometry of the basins.